2017
DOI: 10.1093/cvr/cvx187
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-424(322) as a new marker of disease progression in pulmonary arterial hypertension and its role in right ventricular hypertrophy by targeting SMURF1

Abstract: This study shows that miR-424(322) has diagnostic and prognostic value in PH patients, correlating with markers of disease severity. Additionally, miR-424(322) can target proteins with a direct effect on heart function, suggesting that this miRNA can act as a messenger linking pulmonary vascular disease and right ventricle hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 44 publications
2
66
0
1
Order By: Relevance
“…Such an explanation gains some support from a recent study investigating circulating levels of miR‐322‐5p in response to MCT . This study showed that miR‐322‐5p in circulation is elevated 1 week after treatment and then decreases at 2 weeks only to increase again by 6 weeks.…”
Section: Discussionmentioning
confidence: 83%
“…Such an explanation gains some support from a recent study investigating circulating levels of miR‐322‐5p in response to MCT . This study showed that miR‐322‐5p in circulation is elevated 1 week after treatment and then decreases at 2 weeks only to increase again by 6 weeks.…”
Section: Discussionmentioning
confidence: 83%
“…Luckily, a recent study showed that plasma miR-424(322) is significantly up-regulated in the global cohort of pulmonary hypertension (PH) patients and in the subgroup of PAH patients and correlates with the prognosis and severity of disease, and higher levels of miR-424(322) are predictive of event-free survival. 183 Therefore, plasma miR-424(322) is considered to be a unique value biomarker for the diagnosis and prognostic of PH patients. In addition, miR-19a expression is significantly elevated in plasma and in PAH lung tissues, 184 whereas miR-124 expression is down-regulated in blood outgrowth endothelial cells (BOECs) from PAH patients.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…The overall importance of miRNAs in the cardiovascular system was established, such as PAH. Studies revealed that the expression level of miRNAs in human lungs with PAH is changed (Baptista et al, ). Several research tried to explore the effect of miRNAs on the phenotypic change due to enhanced proliferation of pulmonary artery smooth muscle cells (PASMCs) in PAH.…”
Section: Introductionmentioning
confidence: 99%
“…The overall importance of miRNAs in the cardiovascular system was established, such as PAH. Studies revealed that the expression level of miRNAs in human lungs with PAH is changed (Baptista et al, 2018).…”
Section: Introductionmentioning
confidence: 99%